Positive Online Customer Reviews Significantly Boost Sales for Micro-Businesses - Patel, Prisha D. (Integrated Journal for Research in Arts and Humanities, 2024)
Online customer evaluations are a great resource for shoppers, and this study intends to examine them. It highlights the difficulty of making the correct selections from merchant websites because of the abundance of possibilities. The most recent findings about the links and connections between OCRs and consumers' intentions to buy are analyzed in this research. Here we take a look at the most important aspects of OCRs and how these influence consumers' propensity to buy. Many product reviews affect consumers' propensity to make a purchase, with an eye on conversion rates. The author used the Prisma Model, which incorporates 390 studies from different sources (including Google Scholar and 85 extra web pages), to draw our conclusions. The results demonstrated that: (1) customer reviews on the internet positively and significantly impact purchasing decisions and (2) online customer reviews positively and significantly impact trust. Two studies look at how different industries' purchasing patterns are affected by consumer feedback. Bringing attention to the impact of reviews on awareness and persuasive outcomes.